PENDIDIKAN KESEHATAN TENTANG DAMPAK PENGGUNAAN GADGET PADA ANAK USIA DINI DI TK AL-HIDAYAH KOTA JAMBI: DAMPAK PENGGUNAAN GADGET PADA ANAK USIA DINI DI TK AL-HIDAYAH KOTA JAMBI - Nengsih, Novida; Andini, Febri Tri (Jurnal Pengabdian Masyarakat, 2025)
Background: Rapid technological developments have led to an increase in the use of gadgets in early childhood, which has the potential to have negative impacts on their growth and development, such as impaired language development, concentration, and social interaction. Therefore, health education about the impacts of gadget use is very much needed to increase the awareness of parents and teachers in managing gadget use in children. Objective: To provide education to early childhood about the impacts of gadget use in Al-Hidayah Kindergarten, Jambi City Method: The method used in this community service is a counseling method by providing health education about the impacts of gadget use in early childhood in Al-Hidayah Kindergarten, Jambi City. The method used involves LCD media to convey material in the form of illustrated stories, and is accompanied by the provision of leaflets that can be reread at home with parents. Results: children begin to understand the positive and negative impacts of gadget use, as well as the importance of managing gadget use time Conclusion: interesting and participatory education is effective in forming wise behavior in gadget use in early childhood. It is hoped that parents and teachers will continue to supervise and provide alternative activities that support children's physical and social development without relying on gadgets. Keywords: Gadget; Early Childhood, Health Education